Multigenerational exposure of cadmium trans-generationally impairs locomotive and chemotactic behaviors in Caenorhabditis elegans. (June 2023) - Zhang, Jun; Yang, Wenxing; Li, Zhuo; Huang, Feijun; Zhang, Kui
Abstract: Cadmium is a naturally existing heavy metal and a notorious environmental pollutant. While its toxic outcomes and underlying mechanisms remain largely elusive. To explore the behavioral change caused by multigenerational exposure of cadmium to C. elegans, we challenged the C. elegans with cadmium for six generations and observed its impact on animal behaviors. Wild-type worms were randomly divided into two groups, the control and cadmium exposure groups. Locomotive and chemotactic behaviors were observed across six generations. Head thrashing frequency, chemotaxis index, and fold change index were used to evaluate the neurotoxicity of multigenerational cadmium exposure. Multigenerational cadmium exposure can trans -generationally increase the head thrashing frequency of C. elegans during swimming, and impair the chemotactic behaviors to isoamyl alcohol, diacetyl, and 2-nonanone. Our findings proposed a trans -generationally behavioral impact induced by multigenerational cadmium exposure. Graphical abstract: Image 1 Highlights: The multigenerational behavioral impact of cadmium was evaluated by C. elegans. The multigenerational exposure to cadmium in C. elegans trans -generationally impaired chemotaxis and chemo-avoidance. Trans -generationally impaired chemotaxis was observed in both chemotaxes to attractant and chemo-avoidance to repellent. Impairment in chemotaxis to attractant seems to be more severe than that in chemo-avoidance to repellent.